Xây dựng hệ thống thông tin quản lý tài nguyên môi trường - Ý, Trần Văn; Trí, Ngô Đăng; Hiển, Nguyễn Đức; Hiếu, Nguyễn Công; Tuấn, Nguyễn Thanh; Quên, Nguyễn Hạnh (Vietnam Journal of Earth Sciences, 2005)
REMIS is a system designed for making decision process in resource and environment management. At least the REMIS contains three component : technical facility, staff and information one. In this paper the authors presented information parts of a system : in information database, predictive models and the tools designed to support the resource and environment manager in making decision process for the Quang Tri province. The understandings of the data, information, knowledge, wisdom and the nature of resource and evironment managenent in context with the REMIS are also explained in detail.